Expanding tactics for listening: Teacher's book More listening. More testing. More effective - Richards, Jack C.; Trew, Grant (Oxford New York Oxford University Press, 2011)
This third level of a three-level series that gives intermediate students who have studied English previously extensive practice in understanding everyday conversational language. There are 24 unit lessons accompanied by tactics for testing materials to assist students with the listening sections of the TOEIC test, the TOEFL test, IELTS, and other exams.
Keywords: Ngôn ngữ Anh